Call for Papers og sammendrag av samtlige foredrag - Aspaas, Per Pippin; Davenport, Randi Lise; Klein, Andreas; Nilsen, Fredrik; Himmelmann, Beatrix; Rasmussen, Siv; Evju, Håkon Andreas (Septentrio Conference Series, 2021)
This issue of Septentrio Conference Series provides documentation of the digital conference "Nature and the Natural in the Eighteenth Century", organized by the Norwegian Society for Eighteenth-Century Studies on 3–5 February 2021. The Call for Papers (as published in Norwegian on www.1700-tallet.no on 9 September 2020) as well as the final programme with abstracts of all papers are included in PDF format. The keynote lectures were recorded by means of Zoom. Other papers were not recorded.